2019
DOI: 10.1089/jpm.2018.0338
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Barriers to Introducing Early Palliative Care for Patients with Advanced Cancer: A Qualitative Study

Abstract: Background: Palliative care is often underutilized or initiated late in the course of life-threatening illness. Randomized clinical Early Palliative Care (EPC) trials provide an opportunity for changing oncologists' perceptions of palliative care and their attitudes to referring patients to palliative care services. Aim: To describe French oncologists' perceptions of EPC and their effects on referral practices before a clinical EPC trial was launched. Design: A qualitative study involving semistructured face-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 67 publications
0
81
0
9
Order By: Relevance
“…However, early and correct diagnosis has been a major challenge in healthcare institutions, due to a number of institutional barriers, such as a lack of sufficient beds for palliative patients, an inadequate number of palliative care committees, non-uniformity of training for health professionals on palliative care and few palliative care programs in health institutions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, early and correct diagnosis has been a major challenge in healthcare institutions, due to a number of institutional barriers, such as a lack of sufficient beds for palliative patients, an inadequate number of palliative care committees, non-uniformity of training for health professionals on palliative care and few palliative care programs in health institutions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Effects on mortality and depression remained uncertain [4]. The results of qualitative studies performed in different countries suggested that the early integration of specialised palliative care is well accepted by patients, relatives and, to a lesser extent, oncologists [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of these patients remains sub-optimal and occurs too late in the illness trajectory and more particularly with non-oncological diseases, which have more unpredictable trajectories (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%